PENGARUH INTELLECTUAL CAPITAL PADA KINERJA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BEI - Aisah, Dewi Siti; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out the influence of intellectual capital which is proxy by Public model (VAICTM) to the performance of the company which is proxy by market to book value (MB) on the automotive sector companies. The population is automotive companies which are listed in Indonesia Stock Exchange (IDX). In this research, the sample collection has been done by using purposive sampling, and 12 samples automotive companies which have published consecutively their financial statement in 2010-2014 periods. This research has been done by using multiple linear regressions.The result of this research shows that: (1) The value added capital employed (VACA) variable has positive influence and shows unidirectional relationship between VACA and MB; (2) the value added human capital (VAHU) variable has positive influence and shows unidirectional relationship between VAHU and MB; (3) structural capital value addded (STVA) ) variable has significant influence to the MB yet the negative regression coefficient shows the non-unidirectional relations between STVA and MB.Keywords: intellectual capital, market to book value, value added capital employed, value added human capital, structural capital value added